2022
DOI: 10.3748/wjg.v28.i27.3398
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in liver ultrasound

Abstract: Artificial intelligence (AI) is playing an increasingly important role in medicine, especially in the field of medical imaging. It can be used to diagnose diseases and predict certain statuses and possible events that may happen. Recently, more and more studies have confirmed the value of AI based on ultrasound in the evaluation of diffuse liver diseases and focal liver lesions. It can assess the severity of liver fibrosis and nonalcoholic fatty liver, differentially diagnose benign and malignant liver lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that radiomics based on image features can extract objective characteristics and provide valuable insights in predicting clinical outcomes(28).Indeed, both domestic and international researchers have been exploring the clinical utility of radiomics in diagnosing hepatic steatosis. For example, Chou and colleagues classi ed the severity of hepatic steatosis using patient ultrasound images (29)(30), while Sim and others used radiomics derived from MR-PDFF to diagnose the degree of hepatic fat deposition in NAFLD patients (31).Ultrasound grayscale images indeed contain a wealth of raw image information, including re ections and scattering of small structures within the liver parenchyma (32). In this study, ultrasound radiomics was used to extract image features from these grayscale ultrasound images.After dimension reduction using LASSO, a total of 25 features were retained, and a radiomics model was developed using the K-nearest neighbors (KNN) algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that radiomics based on image features can extract objective characteristics and provide valuable insights in predicting clinical outcomes(28).Indeed, both domestic and international researchers have been exploring the clinical utility of radiomics in diagnosing hepatic steatosis. For example, Chou and colleagues classi ed the severity of hepatic steatosis using patient ultrasound images (29)(30), while Sim and others used radiomics derived from MR-PDFF to diagnose the degree of hepatic fat deposition in NAFLD patients (31).Ultrasound grayscale images indeed contain a wealth of raw image information, including re ections and scattering of small structures within the liver parenchyma (32). In this study, ultrasound radiomics was used to extract image features from these grayscale ultrasound images.After dimension reduction using LASSO, a total of 25 features were retained, and a radiomics model was developed using the K-nearest neighbors (KNN) algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the Rad-score was also an independent predictor of recurrence in PTC. Recently, the US radiomics signatures have been widely used to predict many aspects of tumor behaviors in various organs [ 42 45 ]. And Park et al found that radiomics features extracted from ultrasound images might be potential imaging biomarkers for risk stratification in patients with PTC [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasomics is a branch of radiomics, which can extract a large number of quantitative features from ultrasonic images, including texture, shape, intensity, trend, and wavelet features, etc., which represent different pathological types of diseases, and provide clinicians with comprehensive quantitative phenotypes to help clinical decision-making ( 26 ). The application of ultrasomics has been gradually broadened by the updating of ultrasonic technology and the swift development of computerized algorithms, with studies now being conducted in the areas of thyroid ( 5 ), breast ( 31 ), liver ( 32 ), prostate ( 33 ), and head and neck tumors ( 34 ).…”
Section: Discussionmentioning
confidence: 99%